Oil palm and structural transformation of agriculture in Indonesia - Daniel Chrisendo; Hermanto Siregar; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2020)
Structural transformation of agriculture typically involves a gradual increase of mean farm sizes and a reallocation of labor from agriculture to other sectors. Such structural transformation is often fostered through innovations in agriculture and newly emerging opportunities in manufacturing and services. Here, we use panel data from farm households in Indonesia to test and support the hypothesis that the recent oil palm boom contributes to structural transformation. Oil palm is capital-intensive but requires much less labor per hectare than traditional crops. Farmers who adopted oil palm increase their cropping area, meaning that some of the labor saved per hectare is used for expanding the farm. Average farm sizes increased in recent years. In addition, we observe a positive association between oil palm adoption and off-farm income, suggesting that some of the labor saved per hectare is also reallocated to non-agricultural activities. Oil palm adoption significantly increases the likelihood of households pursuing own non-farm businesses. However, oil palm adoption does not increase the likelihood of being employed in manufacturing or services, which is probably due to the limited non-farm labor demand in the local setting. Equitable and sustainable agricultural transformation requires new lucrative non-agricultural employment opportunities in rural areas.
urn:nbn:de:gbv:7-webdoc-4005-3
Keywords: O13; O14; Q12; Q15; R14; 330; Cross-country dataset; lower-middle income countries; risk preferences; smallholder farmers; time preferences